ANALISIS YURIDIS ATAS PENARIKAN DUKUNGAN PARTAI POLITIK TERHADAP BAKAL PASANGAN CALON YANG TELAH DIDAFTARKAN (STUDI PENYELENGGARAN PILKADA KABUPATEN BINTAN TAHUN 2020) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2021)
Article 6 paragragh (4) and (5) PKPU No.3/2017 along with KPU RI decree Number. 758/PL/02.2-SD/06/KPI/IX/2020 constitute 2(two) contradictory legal principles in ordinance about support revocation of political party against prospective candidate whohas been registered which happened in Bintan regional head election and it creates uncertainty in legal practice. The scope ofthis research are, what the position of KPU RI Decree No. 758/PL/02.2-SD/06/KPI/IX/2020 as an intrument of governmentpolicy regulations? And the binding of the parties’ agreement as stipulated in PKPU No. 3 of 2017? To answer this issues,researches using normative methods (library research) along using statute approach. The results of this research are, first, theKPU RI decree No. 758/PL/02.2-SD/06/KPI/IX/2020 which categorized as policy regulations are not suitable as the purpose,scope and terms from discretion as have been regulated on Government Administrative Constitution; second, political partymakes an agreement with the prospective candidate to registered for the election (article 6 paragraph (3) PKPU No. 3 of 2017),according to contract law must be seen as a covenants that has delivered agreement for the parties who has been agree to thecovenant.